PERANCANGAN ULANG UI/UX DESIGN APLIKASI IDENTITAS KEPENDUDUKAN DIGITAL MENGGUNAKAN METODE USER CENTERED DESIGN (UCD) - Ilhamudin Firdaus, Tendy; Defriani, Meriska; Dewi Lestari, Candra (INFOKOM (Informatika & Komputer), 2023)
Digital ID or Digital Population Identity is an important innovation by the Directorate General of Civil Registration of the Ministry of Home Affairs in Indonesia to digitize population documents and provide easy access to Indonesian citizens through their mobile phones. Although the Digital Population Identity application has gained significant popularity with a rating of 3.4 on the Play Store and thousands of user reviews, observations from user feedback have revealed several challenges that hinder users from utilizing the application according to their needs. The initial evaluation using the System Usability Scale (SUS) method indicates the need for improvements in the interface of the Digital Population Identity application, despite receiving a "Good" rating with a score of 54.13. In this study, the User-Centered Design (UCD) method was employed to redesign the UI/UX of the application, considering user needs and experiences. The results of the UI/UX design using the UCD method successfully addressed the identified issues. The addition of features such as login functionality, QR code verification via email, automatic face verification, document download, and a redesign of the application’s interface significantly improved the final evaluation score to 76.5 with an "Excellent" rating. This indicates that the implemented enhancements have successfully improved the application’s interface and better meet user needs.